A Microbiomic Analysis of a Pasture-Raised Broiler Flock Elucidates Foodborne Pathogen Ecology Along the Farm-To-Fork Continuum - Rothrock, Michael J.; Locatelli, Aude; Feye, Kristina M.; Caudill, Andrew J.; Guard, Jean; Hiett, Kelli; Ricke, Steven C. (Frontiers in Veterinary Science, 2019)
While conventionally grown poultry continues to dominate the U.S. poultry industry, there is an increasing demand for locally-grown, “all natural” alternatives. The use of next generation sequencing allows for not only the gross (e.g. community structure) but also fine-scale (e.g. taxa abundances) examination of these complex microbial communities. This data provides a better understanding of how a pasture flock’s microbiome changes throughout the production life cycle and how that change in microbial ecology changes foodborne pathogens in alternative poultry production systems. In order to understand this ecology better, pooled broiler samples were taken during the entire flock life cycle, from pre-hatch gastrointestinal samples (N=12) to fecal samples from the brood (N=5) and pasture (N= 10) periods. Additional samples were taken during processing, including skin and feather rinsates (N=12), ceca (N=12), and whole carcass rinses (N = 12), and finally whole carcasss rinsates of final products (N=3). Genomic DNA was extracted, 16S rDNA microbiome sequencing was conducted (Illumina MiSeq), and microbiomes were analyzed and compared using QIIME 1.9.1 to determine how microbiomes shifted throughout production continuum, as well as what environmental factors may be influencing these shifts. Significant microbiome shifts occurred during the life cycle of the pasture broiler flock, with the brood and pasture fecal samples and cecal samples being very distinct from the other pre-hatch, processing and final product samples. Throughout these varied microbiomes, there was a stable core microbiome containing thirteen taxa. Within this core microbiome, five taxa represented known foodborne pathogens (Salmonella, Campylobacter) or potential/emerging pathogens (Pseudomonas, Enterococcus, Acinetobacter) whose relative abundances varied throughout the farm-to-fork continuum, although all were more prevalent in the fecal samples. Additionally, of the twenty-five physiochemical and nutrient variables measured from the fecal samples, the carbon to nitrogen ratio was one of the most significant variables to warrant further investigations because it impacted both general fecal microbial ecology and Campylobacter and Enterococcus taxa within the core fecal microbiomes. These findings demonstrate the need for further longitudinal, farm-to-fork studies to understand the ecology of the microbial ecology of pasture production flocks to improve animal, environmental, and public health.